(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Polycrystalline spinel MgxZn0.3Cu0.7-2xFe2+xO4, where x = 0.10, 0.20, 0.25, 0.30 and 0.35 ferrites (hereafter abbreviated as Mg-Zn) have been prepared by conventional double sintering technique. The samples were sintered at 1250°C in air for 6 hours. Measurements have been done at temperature and frequency ranges of 0 - 350°C and 0 - 500 kHz, respectively. In this work, some extrinsic magnetic properties such as Curie temperature, initial permeability, loss factor, quality factor, dielectric constant and resistivity of the samples have been studied. The Curie temperature and loss tangent of the samples decreased with increase in Cu-content whereas permeability, Qfactor, resistivity and dielectric constant have been noticed to be increased with the increase in Cucontent. The decrease in Curie temperature related to fact of weakening the strength of exchange AB interaction. Maxwell-Wagner type of interfacial polarization might have found correlated with the normal dielectric behavior of the samples, however no relaxation peaks were observed in the dielectric dispersion curves of the Mg-Zn samples in virgin state or doped state. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12963 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 199-212, 2012